Survival Rate and Factors Affecting on Survival of Early-Stage Epithelial Ovarian Cancer Patients at Sawanpracharak Hospital - Yotwimonwat, Tidaporn (Srinagarind Medical Journal, 2024)
Background and Objective: Although the survival rate of early-stage epithelial ovarian cancer is higher than advanced-stage cancer, approximately 20% to 30% of these patients succumb to the disease. The main objective is to study the 5-year survival rate, with secondary objectives focusing on factors influencing the survival of patients with early-stage epithelial ovarian cancer. Methods: This research is a retrospective cohort study of a population comprising patients diagnosed with early-stage epithelial ovarian cancer who received treatment at Sawanpracharak Hospital between January 1, 2008, and December 31, 2018. Data were collected from medical records, and statistical analysis involved descriptive statistics, Kaplan-Meier survival curve, Log-rank test, and Cox proportional hazard model with a significance level set at p < 0.05. Results: Among 151 patients with early-stage epithelial ovarian cancer, with a median follow-up time of 101 months, the 5-year disease-free and overall survival rates were 79.3% and 80.2%, respectively. Stage 1 ovarian cancer had a 5-year disease-free and overall survival rate of 81.3% and 83.4%, while stage 2 had rates of 71.9% and 71.7%, respectively. In the multivariate analysis, the results indicate that ECOG PS 2,3 (HR 8.84, 95% CI 2.88-27.07, p=0.001), (HR 10.68, 95% CI 3.99-28.57, p<0.001), and clear cell cancer (HR 9.01, 95% CI 1.91-42.39, p=0.005), (HR 5.16, 95% CI 1.44-18.49, p=0.012), serve as independent predictive factors for a poorer 5-year disease-free survival (DFS) and overall survival (OS). Women who were administered the carboplatin regimen (HR 5.79, 95% CI 1.12-29.61, p=0.036) and the carboplatin plus cyclophosphamide regimen (HR 3.64, 95% CI 1.22-10.89, p=0.021) exhibited lower 5-year progression-free survival (PFS) and 5-year OS compared to those who received the carboplatin plus paclitaxel regimen, respectively. Conclusion: Early-stage epithelial ovarian cancer demonstrates favorable disease-free and overall survival rates when treated with adequate surgery and chemotherapy.